Tracing North Atlantic volcanism and seaway connectivity across the Paleocene–Eocene Thermal Maximum (PETM) - M. T. Jones; E. W. Stokke; A. D. Rooney; J. Frieling; P. A. E. Pogge von Strandmann; D. J. Wilson; H. H. Svensen; S. Planke; T. Adatte; N. Thibault; M. L. Vickers; T. A. Mather; et al. (Climate of the Past, 2023)
There is a temporal correlation between the peak activity of the North Atlantic Igneous Province (NAIP) and the Paleocene–Eocene Thermal Maximum (PETM), suggesting that the NAIP may have initiated and/or prolonged this extreme warming event. However, corroborating a causal relationship is hampered by a scarcity of expanded sedimentary records that contain both climatic and volcanic proxies. One locality hosting such a record is the island of Fur in Denmark, where an expanded pre- to post-PETM succession containing hundreds of NAIP ash layers is exceptionally well preserved. We compiled a range of environmental proxies, including mercury (Hg) anomalies, paleotemperature proxies, and lithium (Li) and osmium (Os) isotopes, to trace NAIP activity, hydrological changes, weathering, and seawater connectivity across this interval. Volcanic proxies suggest that NAIP activity was elevated before the PETM and appears to have peaked during the body of the δ 13 C excursion but decreased considerably during the PETM recovery. This suggests that the acme in NAIP activity, dominated by flood basalt volcanism and thermogenic degassing from contact metamorphism, was likely confined to just ∼ 200 kyr (ca. 56.0–55.8 Ma). The hundreds of thick ( > 1 cm) basaltic ashes in the post-PETM strata likely represent a change from effusive to explosive activity, rather than an increase in NAIP activity. Detrital δ 7 Li values and clay abundances suggest that volcanic ash production increased the basaltic reactive surface area, likely enhancing silicate weathering and atmospheric carbon sequestration in the early Eocene. Signals in lipid biomarkers and Os isotopes, traditionally used to trace paleotemperature and weathering changes, are used here to track seaway connectivity. These proxies indicate that the North Sea was rapidly cut off from the North Atlantic in under 12 kyr during the PETM recovery due to NAIP thermal uplift. Our findings reinforce the hypothesis that the emplacement of the NAIP had a profound and complex impact on ...